2015
DOI: 10.1371/journal.pone.0145133
|View full text |Cite
|
Sign up to set email alerts
|

A Vivens Ex Vivo Study on the Synergistic Effect of Electrolysis and Freezing on the Cell Nucleus

Abstract: Freezing—cryosurgery, and electrolysis—electrochemical therapy (EChT), are two important minimally invasive surgery tissue ablation technologies. Despite major advantages they also have some disadvantages. Cryosurgery cannot induce cell death at high subzero freezing temperatures and requires multiple freeze thaw cycles, while EChT requires high concentrations of electrolytic products—which makes it a lengthy procedure. Based on the observation that freezing increases the concentration of solutes (including pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…The first study employed a protocol in which electrolysis was delivered first, followed by freezing. Experiments on animal tissue have confirmed our hypothesis and have shown that cryoelectrolysis is more effective at cell ablation than either cryosurgery or electrolytic ablation, alone (Lugnani et al, 2015). …”
Section: Introductionsupporting
confidence: 65%
See 4 more Smart Citations
“…The first study employed a protocol in which electrolysis was delivered first, followed by freezing. Experiments on animal tissue have confirmed our hypothesis and have shown that cryoelectrolysis is more effective at cell ablation than either cryosurgery or electrolytic ablation, alone (Lugnani et al, 2015). …”
Section: Introductionsupporting
confidence: 65%
“…Diffusion and iontophoresis driven electro-osmosis, are the physical mechanisms that cause the propagation of the pH front from the electrode outward. The electro-osmotic flow is an important aspect of electrolytic ablation in tissue (Lugnani et al, 2015; Phillips et al, 2015a; Phillips et al, 2015b; Rubinsky et al, 2015; Rubinsky et al, 2016). The flow is from the anode to the cathode.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations